“Fracture Resistance Of Different Endodontic Niti Rotary File Systems: A Narrative Review” - Shalini Singh; Kailash Attur; Kamal P Bagda; Amar Thakare; Sneha H Choudhary; Nidhi Vatsyayan (Revista Electronica de Veterinaria, 2024)
Nickel-Titanium (NiTi) rotary file systems have become a cornerstone in endodontic therapy, significantly enhancing the efficacy of root canal treatments. Despite their benefits, the risk of file fracture remains a notable concern. This narrative review aims to evaluate and compare the fracture resistance of several prominent NiTi rotary file systems, including Trunatomy, ProTaper Gold, 2Shape, HyFlex CM, and HyFlex EDM. By examining the impact of file design, heat treatment, and operational conditions on fracture resistance, this review synthesizes findings from key studies to provide a comprehensive understanding of how different systems perform under various clinical scenarios.Clinicians can use this information to make informed decisions about file selection based on specific endodontic challenges and canal characteristics. The insights gained from this review are intended to guide best practices in endodontics and reduce the risk of file-related complications during root canal procedures.